Developing Android-Based Instructional Media of Economic Subject for Senior High School - Pratiwi, Nyoman Desyana; Haryono, Agung (Unversitas Negeri Malang, 2019)
This research aims at identifying the utilization of YouTube as an instructional media of Economic subject for senior high school students. This research employed a Research and Development approach (R&D). It involved the tenth grader students of SMA Trimurti 01 Pakisaji, Malang Regency. To validate the developed media, it performed product validation which was carried out by media and lesson content experts. In addition, a user test was also administered which involved teacher and students; it was conducted twice. The results confirmed that the media developed is feasible and acceptable to be used which obtained 83.01 percent of an average score.Â